Acquiring skills - Trikojus, Tom (Bendigo, Victoria : Video Education Australasia, 2002)
Summary: This video clearly investigates the basic concepts of acquiring skills and information processing and applies these to human performance. It covers, type of movements, open & closed skills, types of learning, stages of learning, feedback etc.
Executive producer, Mark McAuliffe ; editor, Michael Henry
Keywords: Sport sciences; Individuals